Characterization of Vasoreactivity in a Semi-Arboreal Snake, the Tokara Habu (Protobothrops tokarensis) - Tomoki Ootawa; Siyuan Wu; Ryoya Sekio; Henry Smith; Md. Zahorul Islam; Ha Thi Thanh Nguyen; Yasuhiro Uno; Mitsuya Shiraishi; Atsushi Miyamoto (Animals, 2023)
Vasoreactivity is relatively well documented in terrestrial snakes but has previously been investigated in only one semi-arboreal snake species. Consequently, the extent to which vasoreactivity is common across snake taxa or varies by habitat is unclear. The Tokara habu (Protobothrops tokarensis) is a semi-arboreal snake endemic to only two small adjacent Japanese islands, and hence a useful species for further investigation of vasoreactivity. We evaluated responses to known vasoactive substances in thoracic aortas isolated from Tokara habu. Under resting tension, noradrenaline and angiotensin II induced concentration-dependent contraction, but acetylcholine, serotonin (5-hydroxytriptamine; 5-HT), and isoproterenol induced relaxation followed by contraction. Histamine and rattlesnake bradykinin had no effect. Experiments with receptor-specific antagonists suggest that M1 and M3 receptors are involved in the acetylcholine-induced response; 5-HT1, 5-HT2, and 5-HT7 receptors in the serotonin-induced response; and β1 and β2 adrenoceptors in isoproterenol-induced relaxation. This is the first report on such response patterns in snakes (including serotonin- and isoproterenol-induced relaxation). Nitric oxide may be involved in acetylcholine-induced relaxation but not in the responses to serotonin or isoproterenol. In contrast to the uniform vasoreactivity observed in terrestrial snakes, the vasoreactivity of semi-arboreal snakes may be governed by diverse regulatory mechanisms.